Concomitant chronic lymphocytic leukemia and multiple myeloma: proof of common clonal origin - Sucker, Christoph; Krämer, Alwin; Moos, Marion; Goldschmidt, Hartmut (The Chinese-german journal of clinical oncology, 2004)
We describe a patient with concomitant B-cell chronic lymphocytic leukemia (CLL) and multiple myeloma (MM). CLL- and MM-cell were separated by preparative flourescence-activated cell sorting (FACS). DNA sequence analysis of the complementarity-determinining region III (CDR III) of the immunoglobulin heavy chain genes showed identical gene rearrangements in the CLL- and the MM-cell population. Our findings prove a common clonal tumor origin of both B-cell diseases in this patient.
Gesehen am 11.02.2022